Striving for normality: Agency, citizen participation and intergroup belonging on the urban periphery of Helsinki - Tuominen, Pekka (Frontiers in Sustainable Cities, 2022)
Strive for Normality: Agency, Citizen Participation and Intergroup Belonging in the Urban Periphery of Helsinki This article examines the striving for meaningful encounters in the lives of inhabitants of a culturally diverse suburban estate in Finland that has been plagued by bad reputation since its construction in the 1960s. The focus is on Kontula, a residential working class district in the eastern periphery of Helsinki, which has become a powerful symbol of the ills of contemporary urbanity – poverty and social problems, as well as rootlessness and failed integration of the immigrant populations – in the vernacular geography and media representations of the city. I study how everyday mobility in an increasingly segregated city is related to different qualities of sociocultural encounters, both within the immediate neighbourhood and across other urban areas. I argue that for many marginalised inhabitants agency predominantly emphasises strive for normality, not a challenge to the system. This is why it is so rarely recognised. Themes such as common decency, meaningful activity and equal encounter are much more typical aims of everyday practices than those focussing on changing the conditions. The contexts exploerd range from the familiar and neighbourly surroundings characterised by high degree of cultural intimacy and effortlessness to spaces with unfamiliar expectations and very different cultural codes. How do people living in the stigmatised periphery establish sense of belonging in a segregated city? How is it possible retain a sense of decency and dignity in unpredictable circumstances? During my long-term ethnographic fieldwork in the area, I concentrated on the qualities of different encounters and senses of agency. These are interweaved to the inhabitants’ everyday life, realised in the movement across the city and vary considerably in different contexts, reproducing the quotidian urbanity of Helsinki.